2011
DOI: 10.1111/j.1478-4408.2011.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between colour fastness and colour strength of polypropylene fabrics dyed in supercritical carbon dioxide: effect of chemical structure in 1,4‐bis(alkylamino)anthraquinone dyestuffs on dyeing performance

Abstract: A series of 1,4‐bis(alkylamino)anthraquinone dyestuffs were applied for supercritical fluid dyeing of unmodified polypropylene fabric, which is known to be difficult to dye in a conventional aqueous system. A marked tendency was shown that the dyeability improved as the carbon number of alkyl substituents on the anthraquinone chromophore increased. By evaluating the build‐up curves of the dyestuff, it was found that the carbon number of optimum alkyl chain length for 1,4‐bis(alkylamino)anthraquinone was 8–12. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Dyeing polypropylene (PP) fibres with commonly used methods is extremely difficult because of their high crystallinity and non‐polar aliphatic structure, which does not contain any sites to which certain types of dye may bind . Studies on PP dyeing in an aqueous system showed that dyestuffs with higher hydrophobicity than those commonly used for PET dyeing are required .…”
Section: Supercritical Dyeing Of Other Synthetic Fibresmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyeing polypropylene (PP) fibres with commonly used methods is extremely difficult because of their high crystallinity and non‐polar aliphatic structure, which does not contain any sites to which certain types of dye may bind . Studies on PP dyeing in an aqueous system showed that dyestuffs with higher hydrophobicity than those commonly used for PET dyeing are required .…”
Section: Supercritical Dyeing Of Other Synthetic Fibresmentioning
confidence: 99%
“…Studies on PP dyeing in an aqueous system showed that dyestuffs with higher hydrophobicity than those commonly used for PET dyeing are required . Therefore, supercritical dyeing of PP could be a suitable alternative . Tests with different classes of disperse dyes were performed and it was found that the dyeability of PP improved when both the hydrophobicity and aliphaticity of the dye were high .…”
Section: Supercritical Dyeing Of Other Synthetic Fibresmentioning
confidence: 99%
“…According to recent research [30], the affinity of a series of 1,4‐bis(alkylamino)anthraquinone dyestuffs to polypropylene fibres increased as the alkyl chains on the molecule became longer, and the dyestuff with alkyl chains shorter than isopropyl was not able to sorb into polypropylene fibres. For comparison, the aliphatic ratios of a series of 1,4‐bis(alkylamino)anthraquinone dyestuffs are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…According to studies on polypropylene dyeing in an aqueous system, the dyestuffs for extremely hydrophobic fibres such as polypropylene require a more extreme hydrophobicity than the dyestuffs commonly used for polyester fibres [23–29]. In our recent study [30], also on scCO 2 , the highly hydrophobic dyestuffs were suitable for dyeing polypropylene fibre. It seems that the dyeing properties are related to the structural character of the molecule of the dyestuff.…”
Section: Introductionmentioning
confidence: 95%
“…As a consequence in the last few decades, various researchers focused their efforts on the synthesis of new dyes for these fibers [7][8][9][10][11][12]. The success of dyeing synthetic textiles, particularly polyester [13][14][15][16][17][18][19][20][21][22][23], with disperse dyes in scCO2 prompted research application of this technique to other synthetic fibers such as polypropylene [24], and aramid fibers [25] or alternative natural fabrics like cotton [26][27][28].…”
Section: Introductionmentioning
confidence: 99%